Serum Albumin Level Adjusted Progesterone Level on the Trigger Day is Not a Significant Predictor of Clinical Pregnancy - Yayla Abide, Cigdem; Ozkaya, Enis; Kayatas Eser, Semra; Devranoğlu, Belgin; Bilgic, Bulent Emre; Kutlu, Tayfun (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: We aimed to assess the effect of serum albumin level adjusted progesterone levels on the trigger day on clinical pregnancy rate in ICSI cycles. Study Design: A total of 100 women undergoing ICSI cycles due to poor ovarian reserve or tubal factor infertility were included in this study. Serum progesterone and albumin levels on the trigger day were utilized to predict clinical pregnancy among normal and poor responders. Results: There were significant differences between groups with and without successful clinical pregnancy in terms of serum albumin (4.6 vs. 4.3 g/dl), progesterone levels (0.5 ng/mL vs. 0.7 ng/mL) on the trigger day and endometrial thickness (11.5 mm vs. 9.3 mm) (p<0.05, p<0.05 and p<0.05, respectively). In ROC analyses, progesterone level on the trigger day was found to be a significant predictor of clinical pregnancy (AUC=0.652, p=0.015). An optimal cut-off value of 0.55 ng/mL was obtained with 65% sensitivity and 57% specificity. Albumin level adjusted progesterone concentrations on the trigger day were 0.67 ng/mL versus 0.64 ng/mL, but this difference was not statistically significant (p>0.05). Conclusion: Albumin adjusted progesterone concentrations may be utilized to determine cases for a freeze-all policy.